Simulação da deriva de clomazone e glyphosate em mudas de laranjeira ‘hamlin’ - Foresti, Eduardo Revoredo [UNESP]; Nepomuceno, Mariluce Pascoina [UNESP]; Alves, Pedro Luis Da Costa Aguiar [UNESP] (FapUNIFESP (SciELO), 2015)
In citrus area of the State of São Paulo it is common that the orange and the sugar cane crops are neighboring. To provide a cost reduce, alcohol and sugar sectors are looking for optimizing their applications, for example, by aerial applications, a practice that increases the risk of drifting of these products in non-target crops. Therefore, this study aimed to evaluate the effects caused by drift simulation of clomazone, itself or followed by glyphosate application in the growth of young plants of orange ‘Hamlin’. The experimental design was randomized blocks with treatments arranged in a 2x8 factorial design, the treatments consisting of two herbicides (clomazone isolated and glyphosate 0.75% pc + clomazone) and eight increasing doses of clomazone (0, 1.56, 3.12, 6.25, 12.50, 18.75, 25.00 and 50.00% of the recommended rate for weed control) with three replicates. At 10 and 90 days after application (DAA) were evaluated stem diameter, length of the branches and the total chlorophyll content, and at 90 DAA were also evaluated leaf area, dry matter of leaves and stem. The results indicated that there was significant reduction in the evaluated characteristics, and the negative effects occur even at low doses at the crop (1,56%), that were able to damage the culture growth. From the results obtained in this study, it can be concluded that the drift of clomazone alone or without following the glyphosate causes losses in the initial growth of the orange, acting more aggressively when in sequence with glyphosate drift.
Drift simulation of clomazone and glyphosate in orange ‘hamlin’ seedlings
Keywords: Citrus; Herbicides; Phytotoxicity